Actual approach to varicosities; our sclerotherapy technique at out-patient clinic with office-based settings, in operating room or instead of operation (Annals of Medical Research, 2021)
None
Keywords: Varicose Vein; Reticular Vein; Telangiectasia; Sclerotherapy.